1980
DOI: 10.1002/kin.550121212
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of azomethane–propane mixtures. Arrhenius parameters for the hydrogen abstraction reactions of methyl with azomethane and with propane

Abstract: Mixtures of up to 14% azcjmethane in propane have been photolyzed using mainly 366 nm radiation in the ranges of 323-453 K and 25-200 torr. Detailed measurements were made of the yields of nitrogen, methane, and ethane. Other products observed were isobutane, n-butane, ethene, and propene. A detailed mechanism is proposed and shown to account for the observed variation of product yields with experimental conditions. The quantum yield of the molecular processis found to be given by the temperature-independent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…These authors, however, were not concerned with any possibilities of structure changes of the glass during the reaction. It has already been confirmed that the stoichiometric glass is stable below the glass transition region (T,) and crystallization occurs on long time heating above 700°C [8,9]. However, this is not the case for nonstoichiometric glasses, which are expected to be produced during the reduction.…”
Section: Introductionmentioning
confidence: 99%
“…These authors, however, were not concerned with any possibilities of structure changes of the glass during the reaction. It has already been confirmed that the stoichiometric glass is stable below the glass transition region (T,) and crystallization occurs on long time heating above 700°C [8,9]. However, this is not the case for nonstoichiometric glasses, which are expected to be produced during the reduction.…”
Section: Introductionmentioning
confidence: 99%